Clean energy technology adoption, cultural differences and basic human dispositions - Sharma, Swati (Nanyang Technological University, 2021)
As the responsibility to adopt a residential clean energy system ultimately lies with an individual, it is crucial to understand what makes an individual to adopt clean energy technologies-- A critical question that this dissertation considers. Most existing studies have recognized socio-demographics, financial incentives, and legislations as the fundamental determinants of clean energy adoption. I go beyond this conventional wisdom and take a novel approach for understanding the adoption patterns of clean energy technologies, climate change policies, and overall energy-saving behavior. I take a comparatively unique approach that involves exploring the role of cultural differences and basic human dispositions in explaining such chaste technical aspects. I use different empirical methods, i.e., using cross-sectional and longitudinal databases based on global public opinion surveys, and experimental approaches by conducting self-designed experiments. Particularly, the dissertation comprises three self-contained essays that empirically explore the link between major cultural dimensions and various clean energy adoption and policy aspects. The first essay (chapter 2) explores the variations in individual-level clean energy adoption across countries and their potential determinants. Particularly, I aim to understand the role of cultural differences in the form of individualism vs. collectivism in shaping the adoption of residential clean energy systems. Using data of individualistic orientations and actual clean energy adoption for about 25,000 individuals across 33 countries, this study finds that people with individualistic orientations are more inclined to adopt clean energy systems for home and transport purposes. The adoption probability rises by an estimated 2% if a person exhibits individualistic values. As findings of the study show that individualists are likely to adopt clean energy technology adoption, policy intervention using taxes and subsidies should have a greater priority in collectivistic cultures. Furthermore, marketing and information programs can be designed on the basis of the individualism vs. collectivism dimension. Such approaches might be crucial to meet the European Commission’s renewable energy targets for EU nations. The next essay (chapter 3) examines the underlying determinants of countries’ ability and willingness to address climate change by focusing on yet another dimension of culture- religiosity. The study investigates whether differences in its population’s level of religiosity may help to explain a country’s ability to adopt stringent climate change policies, both in terms of international commitments and national efforts. The study develops a new index, titled climate change policy stringency” (CCPS), for comparing the stringency of climate change 9 policies of countries across the globe. Based on a cross-section of 75 countries, the linear regression analysis suggests that countries with populations showing greater religious fervor tend to adopt less stringent climate change policies. The findings shed light on how religiosity- a cultural dimension- affects contemporary policy outcomes. This novel knowledge may help policymakers in identifying obstacles to climate change policies. For instance, in more religious societies; climate change awareness campaigns, public reach out, and persuasion programs should focus on founding the climate change urgency appeal around the religious beliefs of people. Ultimately, the increased public acceptance of climate change actions may also influence legislators’ support for such policies and help meet the global emission reduction targets. The final essay (chapter 4) explores the role of a significant human disposition- empathic concern- in shaping the energy-use behavior of people. Empathic concern can be defined as the ability to feel warmth, care, and concern for others. For analyzing and measuring empathic concern and energy-saving behavior of people, the study carried out three experimental studies (Study 1: N = 174, Study 2: N = 171, Study 3: N = 175) that involve realistic decision-making scenarios requiring to balance energy use in a space with other occupants’ needs. In particular, I presented participants with diverse and socially complex decision-making scenarios involving conflicting emotions related to participants’ immediate kin (i.e. family) and close in-groups (i.e. co-workers). The findings show that higher levels of empathic concern are associated with energy-saving behavior. Importantly, participants’ energy-saving behavior remains associated with their level of empathic concern even when the energy-use decisions affect others (co-workers or family members), despite that behavior also being influenced by monetary considerations and the need to ensure the comfort of others. These results improve existing models of energy-saving behavior by highlighting that, beyond financial and legislative motives, the capacity to consider and act on other’s welfare could drive energy-saving behavior – even at the expense of the comfort of co-workers and family. Government authorities, policymakers, and social marketers aiming to understand, and influence people’s energy choices might benefit from the present findings by considering the empathic conflicts that consumers might experience. In sum, the findings of all three essays show that it is important to account for cultural differences (i.e., individualism vs. collectivism), degree of religiosity in a country, and also basic human traits (i.e. empathic concern) to accelerate the dissemination of clean energy, promote the energy-saving behavior and address climate change effectively.